Internalization of Tolerance Values Based on Ahlussunnah Wal Jamaah as the Foundation for Harmony in Social Life - Yuliawati Yuliawati; Ahmad Khori; M.Mujib Qulyubi; Yuddy Chandra; Putra Bhakti Satria Utama; Agus Gustapul Supyan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Indonesia’s plural social structure, marked by diversity in religion, ethnicity, culture, and religious perspectives, represents both a social asset and a potential source of tension when not supported by adequate tolerance. The increasing trend of exclusivism, intolerance, and religion-based conflict indicates the urgency of strengthening ethical frameworks capable of fostering harmonious coexistence. This study aims to analyze the process of internalizing tolerance values within the Ahlussunnah wal Jamaah (Aswaja) perspective and to examine its implications for social harmony in a pluralistic society. A qualitative approach was employed through library research, utilizing secondary data from scholarly books, journal articles, and relevant academic publications. Data were analyzed using content analysis to identify key concepts related to tolerance, Aswaja principles, and their social manifestations. The findings show that tolerance in the Aswaja framework is grounded in the principles of tasamuh (tolerance), tawassuth (moderation), tawazun (balance), and ta‘adul (justice), which are internalized through cognitive understanding, affective appreciation, and behavioral practice. This internalization process is facilitated by religious education, social-religious activities, and the exemplary role of religious leaders. The study further reveals that the internalization of Aswaja-based tolerance values contributes significantly to the development of mutual respect, the prevention of religion-based social conflict, the strengthening of social solidarity and cohesion, and the reinforcement of national unity. These values function not only as theological principles but also as a socio-ethical foundation for inclusive, peaceful, and civilized social relations in Indonesia’s diverse society.